A CD200R-CD28 fusion protein appropriates an inhibitory signal to enhance T-cell function and therapy of murine leukemia - Oda, Shannon K; Daman, Andrew W; Garcia, Nicolas M; Wagener, Felecia; Schmitt, Thomas M; Tan, Xiaoxia; Chapuis, Aude G; Greenberg, Philip D (Blood, 2017)
Acute myeloid leukemia (AML), the most common adult acute leukemia in the United States, has the poorest survival rate, with 26% of patients surviving 5 years. Adoptive immunotherapy with T cells genetically modified to recognize tumors is a promising and evolving treatment option. However, antitumor activity, particularly in the context of progressive leukemia, can be dampened both by limited costimulation and triggering of immunoregulatory checkpoints that attenuate T-cell responses. Expression of CD200 (OX2), a negative regulator of T-cell function that binds CD200 receptor (CD200R), is commonly increased in leukemia and other malignancies and is associated with poor prognosis in leukemia patients. To appropriate and redirect the inhibitory effects of CD200R signaling on transferred CD8 T cells, we engineered CD200R immunomodulatory fusion proteins (IFPs) with the cytoplasmic tail replaced by the signaling domain of the costimulatory receptor, CD28. An analysis of a panel of CD200R-CD28 IFP constructs revealed that the most effective costimulation was achieved in IFPs containing a dimerizing motif and a predicted tumor-T-cell distance that facilitates localization to the immunological synapse. T cells transduced with the optimized CD200R-CD28 IFPs exhibited enhanced proliferation and effector function in response to CD200 leukemic cells in vitro. In adoptive therapy of disseminated leukemia, CD200R-CD28-transduced leukemia-specific CD8 T cells eradicated otherwise lethal disease more efficiently than wild-type cells and bypassed the requirement for interleukin-2 administration to sustain in vivo activity. The transduction of human primary T cells with the equivalent human IFPs increased proliferation and cytokine production in response to CD200 leukemia cells, supporting clinical translation. This trial was registered at www.clinicaltrials.gov as #NCT01640301.